Impact of age and FSH treatment on follicular environment, folliculogenesis and endometrial histomorphometry in prepubertal gilts - Alfradique, Vivian Angélico Pereira (2022)
This study investigated the effect of age and FSH treatment on plasma levels of IGF-1 and E2, folliculogenesis, endometrial histomorphometry, biochemical composition of follicular fluid (FF), and on nuclear maturation, gene expression and quality of cumulus-oocytes complexes (COCs) of prepubertal gilts. For this, thirty-five prepubertal gilts were separated according to the age (140 or 160 days), and within each age, gilts were allotted to receive 100 mg of FSH [treated; G140+FSH (n = 10) and G160+FSH (n = 7)] or saline solution [control; G140+control (n = 10) and G160+control (n = 8)]. Before and after FSH treatment, blood was collected for IGF1 and E2 assay (radioimmunoassay), and reproductive tract ultrasound were performed. After 24 h of the last FSH injection, animals were slaughtered and their ovaries and uterus were collected for biometrical and histomorphometrical analysis. The biochemical profile of FF was analyzed in automatic biochemistry analyzer . COCs recovered were morphologically classified and submitted to brilliant cresyl blue (BCB) staining, gene expression (RT-qPCR) and in vitro maturation for subsequent evaluation of nuclear oocyte maturation. The percentage of medium follicles increased (P<0.05) as the same proportion that the percentage of small follicles reduced (P<0.05) in FSH-treated and younger gilts. In addition, the concentration of glucose in FF increased (P<0.05) in FSH-treated and older gilts; in contrast, the concentration of triglycerides decreased (P<0.05) in these same groups of gilts. Increasing of age and FSH stimulation improved (P<0.05) the metaphase II and BCB+ COCs rates and decreased (P<0.05) number of early atretic follicles. Also, changes (P<0.05) on endometrial histomorphometric are caused by FSH treatment and age. However, age and FSH treatment had no impact (P>0.05) on most transcripts’ abundance of selected target genes in COCs. Regarding the effect of age, biometrical data of uterus, plasma levels of IGF-1 and E2 increased (P<0.05) and changes (P<0.05) in uterine and ovaries ultrasound images occurs from 140 to 160 days of age. In conclusion, the increasing of the age and FSH treatment improved oocyte nuclear maturation and stimulated the endometrium epithelium in prepubertal gilts. Also, uterine growth still occurs during 140 and 160 days of age in prepubertal gilts. Keywords: Follicular development. Oocyte. Ovarian stimulation. Pig